Bluesky - Butow, Eric; Bollwitt, Rebecca (--For dummies., 2025)
"Bluesky has been taking the social media world by storm. The platform offers users a high degree of control over what information they view and share, abilities they've lost on other platforms. Bluesky For Dummies serves as your guidebook to navigating the new platform. Learn to import your contacts, control your feed, and share content, with easy-to-follow instructions. This book also shows you how to manage who can contact you and access your content, so you can avoid bots, trolls, and other unsavory characters. For business owners, this Dummies guide is a breath of fresh air--learn how to set up Bluesky for your business and enjoy a peaceful and profitable social experience"--